1997
DOI: 10.1108/00070709710158825
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for wine attributes: a conjoint approach

Abstract: Examines and compares wine attribute preferences within and between two different Spanish regions, Aragón and Navarra, by means of the weighted least squares approach for conjoint analysis. Uses three attributes in the conjoint design: price, origin and grape vintage year. Among these attributes, Navarra consumers assigned more importance to the origin of the wine, followed by price and grape vintage year. Aragón consumers also considered origin as the most important attribute, followed, in this case, by grape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 8 publications
9
118
0
4
Order By: Relevance
“…The product attributes and their possible levels were selected on the basis of the results of two focus groups (n = 16; 8 members per session), data from literature 11,20,26 as well as from the results of a preliminary sensory study which identified sensory properties of NAB beers on sale in Italy (QDA techniques and sensory mapping). The attributes studied included product features such as colour and flavour, marketing mix variables such as price attribution, and structural characteristics such as packaging and general claims.…”
Section: Methodsmentioning
confidence: 99%
“…The product attributes and their possible levels were selected on the basis of the results of two focus groups (n = 16; 8 members per session), data from literature 11,20,26 as well as from the results of a preliminary sensory study which identified sensory properties of NAB beers on sale in Italy (QDA techniques and sensory mapping). The attributes studied included product features such as colour and flavour, marketing mix variables such as price attribution, and structural characteristics such as packaging and general claims.…”
Section: Methodsmentioning
confidence: 99%
“…In the research stream of "stated" preference studies, Gil and Sánchez (1997) used a conjoint designed experiment to examine and compare wine attribute preferences within and between two different Spanish regions. They evaluated the importance of three attributes: price, region of origin and grape vintage year, finding origin to be the most important attribute, but with relevant differences in consumer behavior between regions, in particular in terms of price sensitivity.…”
Section: Rationale and Literature Surveymentioning
confidence: 99%
“…Both models have a long success record and are frequently applied in economics, psychology, consumer research, and related fields, including the domains of travel behavior (e.g., Adamowicz, Louviere, & Williams, 1994;Hensher, 1994;Train, 1978;Wardman, 1988), environmental behavior (e.g., Hanley, Wright, & Adamowicz, 1998;Roberts, Boyer, & Lusk, 2008), political choice behavior (e.g., Bowler, Karp, & Donovan, 2010;Karp, 2009;Nownes, 1992), consumer choices (e.g., Green & Srinivasan, 1978, 1990, or food choices (e.g., Gil & Sánchez, 1997;Loureiro & Umberger, 2005, 2007. For example, using probit models, Ryan and Farrar (2000) analyzed preferences in health care (e.g., treatment in a local clinic vs. treatment in a hospital), and Phillips, Maddala, and Johnson (2002) measured preferences for different HIV tests.…”
mentioning
confidence: 99%